Sistem Kontrol Level Air pada Tandon Air Berbasis Microcontroller dengan Penahan Riak Gelombang - Raka Dian Mahardi; Muhammad ‘Atiq; Sendy Maulana R (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
An automatic water level controller mechanism in a water tank is needed to maintain the availability of water supply. One way is to create a control system that uses an ultrasonic sensor as a detector of the water level that is fed back to the water tank filling pump. To minimize fluctuations in sensor readings, a mechanism is needed to minimize the occurrence of water ripples. To provide easy information to users on site, a monitoring system in the form of an LED indicator is also added that informs the condition of the water level in the water tank. Therefore, in this study, a tool will be created that can automatically control and monitor the water level based on Arduino Uno which uses an ultrasonic sensor and LED indicator with a wave ripple holder